Pertanggungjawaban Pidana Pada Pelaku Penyebaran Dan Jual Beli Konten Pornografi Pada Media Sosial Telegram - Adriansyah Adriansyah; I Wayan Bela Siki Layang (Pusat Riset dan Inovasi Nasional, 2023)
The spread of crime in cyberspace does not escape the crime of pornography, taking advantage of the large storage capacity that Telegram offers has provoked a number of ignorant people to use this social media to spread paid pornographic content. The purpose of this study is to examine and understand what criminal liability and compensation can be imposed on perpetrators of spreading and buying and selling negative content in the Telegram application. Writing scientific journal articles uses a normative research methodology, in which this research uses a statutory approach. The results of the study show that criminal liability that can ensnare perpetrators of pornographic crimes is regulated more specifically based on the principle of lex specialis derogate lex generalis in Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions.